2007
DOI: 10.1007/s11746-007-1083-z
|View full text |Cite
|
Sign up to set email alerts
|

Diesters from Oleic Acid: Synthesis, Low Temperature Properties, and Oxidation Stability

Abstract: Several diesters were prepared from commercially available oleic acid and common organic acids. The key step in the three step synthesis of oleochemical diesters entails a ring opening esterification of alkyl 9,10-epoxyoctadecanoates (alkyl: propyl, isopropyl, octyl, 2-ethylhexyl) using propionic and octanoic acids without the need for either solvent or catalyst. Each synthetic diester was evaluated for both low temperature operability and oxidation stability through measurement of cloud point, pour point, oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 22 publications
(35 reference statements)
2
60
0
1
Order By: Relevance
“…The epoxides will then be subjected to ring-opening reaction under acidic conditions to produce alcohols which will then be subjected to esterification reactions (Adhvaryu et al, 2002). Moser et al (2007) reported improved oxidative stability and fluidity at low temperatures via esterification of alkyl 9,10-epoxyoctadecanoates using propionic and octanoic acids under catalyst-and solvent-free environments.…”
Section: Lubricantmentioning
confidence: 99%
“…The epoxides will then be subjected to ring-opening reaction under acidic conditions to produce alcohols which will then be subjected to esterification reactions (Adhvaryu et al, 2002). Moser et al (2007) reported improved oxidative stability and fluidity at low temperatures via esterification of alkyl 9,10-epoxyoctadecanoates using propionic and octanoic acids under catalyst-and solvent-free environments.…”
Section: Lubricantmentioning
confidence: 99%
“…As shown in Table 1, both WCO PP 2 and CP 4 and SBO PP 8 and CP 0 present a pour point above 10 , which is much higher than their mineral oil counterpart. This can be explained that triglycerides based oils WCO and SBO have a tendency to form macro crystalline structures at low temperature through uniform stacking of the bend triglyceride backbone and such macro crystals limit the easy flow of the fluid due to loss of kinetic energy of individual molecules during self-stacking 9,12,14 . Transforming glycerol group in vegetable oils to other branching alkyl chains would disrupt this stacking process and improve the low-temperature properties of WCO.…”
Section: Low Temperature Propertiesmentioning
confidence: 99%
“…Moser et al reported that the diesters of oleic acid produced by ring opening esterification of epoxidized oleic esters show improved oxidative stability and cold flow property 12 . Gryglewicz and Akermana developed vegetable oil based trimethylolpropane TMP ester from vegetable oils methyl ester through transesterification 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, branching of the alcoholic residue has a beneficial effect in terms of an improved oxidative stability, but is reduced by branched acid chains. While for the alcohol chain a complete H substitution at the β-carbons is particularly favourable, acid chain stability follows the order -CH3 > -CH2-> -CH- [2,13].…”
Section: Introductionmentioning
confidence: 99%